2022
DOI: 10.1039/d2py01167k
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the design and synthesis of biobased epoxy covalent adaptable networks

Abstract: Epoxy thermosets have outstanding physical and chemical properties, but they are unrecyclable/nondegradable due to their permanently crosslinked networks and are also overly dependent on fossil resources. This leads to serious...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 135 publications
0
17
0
Order By: Relevance
“…Significant progress has been made in designing and synthesizing thermoplastic polyacetals (or linear polyacetals), and a more recent study by Coates et al demonstrated the reversible polymerization and depolymerization between polyacetal and a cyclic acetal (i.e., 1,3-dioxolane) monomer . The incorporation of acetal in polymer networks (or thermosets) have also been investigated, and reported efforts include exploring renewable/biobased raw materials, designing degradable networks, ,, and developing reprocessable/recyclable networks. , However, most of the studies only focus on either the degradability or recyclability, and the closed-loop recycling of networks has barely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in designing and synthesizing thermoplastic polyacetals (or linear polyacetals), and a more recent study by Coates et al demonstrated the reversible polymerization and depolymerization between polyacetal and a cyclic acetal (i.e., 1,3-dioxolane) monomer . The incorporation of acetal in polymer networks (or thermosets) have also been investigated, and reported efforts include exploring renewable/biobased raw materials, designing degradable networks, ,, and developing reprocessable/recyclable networks. , However, most of the studies only focus on either the degradability or recyclability, and the closed-loop recycling of networks has barely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, traditional polymers have been challenged by the depletion of petroleum and the price fluctuation of crude oils . In response, tremendous efforts have been devoted to designing and fabricating biobased polymers from renewable resources. , Some biobased thermoplastics such as polylactide and microbial polyester have been commercially available, which have practical applications in biomedical devices, packaging, disposable goods, and electronic products. Biobased thermosets such as epoxies and polyurethanes have also been reported with renewable resources, such as vegetable oils, , furan derivatives, , eugenol, , vanillin, , and lignin, as feedstocks. , Various dynamic covalent bonds have been designed and incorporated into biobased thermosets to develop malleable, recyclable, and multi-functional biobased CANs. Despite this significant progress, biobased CANs and thermosets are still limited by either complex and lengthy fabrication routes or poor mechanical performance. For example, the biobased thermosets or CANs, such as those prepared from commercially available vegetable oils, are limited by the low T g , inferior mechanical strength and poor ductility. Some renewable aromatic compounds derived from natural resources such as vanillin, syringaldehyde, and ferulic acid have been explored to prepare high-performance biobased epoxy thermosets or CANs. However, the fabrication of these polymers usually involves the synthesis and purification of epoxy monomers via costly complex procedures with low purified yields, which makes them commercially uncompetitive. Moreover, all the biobased thermoplastics, CANs, and thermosets are prepared from various renewable chemicals through various synthetic approaches, which enhances the difficulty in the industrial-scale production of these polymers because specific feedstocks and unique equipment and technology are required for each new biobased polymer.…”
Section: Introductionmentioning
confidence: 99%
“…15 In response, tremendous efforts have been devoted to designing and fabricating biobased polymers from renewable resources. 16,17 thermoplastics such as polylactide and microbial polyester have been commercially available, which have practical applications in biomedical devices, packaging, disposable goods, and electronic products. 18−21 Biobased thermosets such as epoxies and polyurethanes have also been reported with renewable resources, such as vegetable oils, 22,23 furan derivatives, 24,25 eugenol, 26,27 vanillin, 28,29 and lignin, as feedstocks.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to their excellent thermal stability, mechanical properties, processing properties, and other advantages, traditional epoxy resins are widely used in aerospace, coatings, electronic communications, solar cells, and other fields. Unfortunately, the production of epoxy resins is heavily dependent on fossil resources, which has severely hindered the further development of epoxy resins. , Meanwhile, as the epoxy thermosetting resin is a permanent cross-linked structure, it is difficult to recycle and reuse. The current treatment methods for discarded, aged, and damaged thermosetting materials are generally incineration or landfilling, which will inevitably cause greater environmental pollution and waste of resources.…”
Section: Introductionmentioning
confidence: 99%